Current state and future perspectives of spinal navigation and robotics—an AO spine survey - Stefan Motov; Vicki M. Butenschoen; Philipp E. Krauss; Anand Veeravagu; Kelly H. Yoo; Felix C. Stengel; Nader Hejrati; Martin N. Stienen (Brain and Spine)
Introduction: The use of robotics in spine surgery has gained popularity. This study aims to assess the current state of robotics and raise awareness of its educational implications. Research question: What are the current adoption trends and barriers to the implementation of robotic assistance in spine surgery? Material and methods: An online questionnaire comprising 27 questions was distributed to AO spine members between October 25th and November 13th, 2023, using the SurveyMonkey platform (https://www.surveymonkey.com; SurveyMonkey Inc., San Mateo, CA, USA). Statistical analyses (descriptive statistics, Pearson Chi-Square tests) and generation of all graphs were performed using SPSS Version 29.0.1.0 (IBM SPSS Statistic). Results: We received 424 responses from AO Spine members (response rate = 9.9 %). The participants were mostly board-certified orthopedic surgeons (46 %, n = 195) and neurosurgeons (32%, n = 136). While 49% (n = 208) of the participants reported occasional or frequent use of navigation assistance, only 18 % (n = 70) indicated the use of robotic assistance for spinal instrumentation. A significant difference based on the country's median income status (p < 0.001) and the respondent's number of annual instrumentation procedures (p < 0.001) has been observed. While 11 % (n = 47) of all surgeons use a spinal robot frequently, 36 % (n = 153) of the participants stated they don't need a robot from a current perspective. Most participants (77%, n = 301) concluded that high acquisition costs are the primary barrier for the implementation of robotics. Discussion and conclusion: Although the hype for robotics in spine surgery increased recently, robotic systems remain non-standard equipment due to cost constraints and limited usability.